PENGEMBANGAN MEDIA PEMBELAJARAN BERBASIS VIDEO DAN BOOKWIDGETS PADA MATERI DAULAH MUGHAL KELAS XI DI MAN KOTA PALANGKA RAYA - Nurlisda,, Nurlisda; Husin, Muhammad Maulana; Arrazin, Muhammad Zaki; Azis, Abdul (Universitas Tanjungpura, 2024)
This research aims to develop learning video media to increase the concentration and understanding of class XI-H students in Man Kota Palangka Raya regarding the Mughal Daula material. and development (RD), Development model 4-D model with data collection techniques in this research namely interviews, observation, documentation and questionnaires. Questionnaires were given to media experts, material experts, SKI teachers and students. The collected data was analyzed using quantitative descriptive analysis techniques. The results of this research show that at the define stage the researcher carried out needs analysis, student analysis and material analysis. The second stage is Design, designing the initial media draft in the form of a storyboard. The third stage of development, the resulting product is a video with the results of material expert validation obtained a validity percentage of 91,7% with the criteria